Short Term Effects of Hurricane Irma and Cyanobacterial Blooms on Ammonium Cycling Along a Freshwater–Estuarine Continuum in South Florida - Hampel, Justyna J.; McCarthy, Mark J.; Reed, Megan H.; Newell, Silvia E. (Frontiers in Marine Science, 2019)
Lacustrine and coastal systems are vulnerable to the increasing number and intensity of tropical storms driven by climate change. Strong winds associated with tropical storms can mobilize nutrients in sediments and alter nitrogen and phosphorus cycling, leading to amplification of preexisting conditions, such as eutrophication and cyanobacterial blooms (cyanoHABs). In 2016, Florida declared a State of Emergency within and downstream of Lake Okeechobee (LO) due to toxic cyanobacterial blooms (primarily Microcystis). The blooms originated in LO, but flood control measures released water from LO to the brackish St. Lucie Estuary (SLE). In September 2017, Hurricane Irma traversed the Florida peninsula with sustained winds exceeding 160 km h-1, generating torrential rains over the watershed. We quantified ammonium (NH4+) regeneration and potential uptake rates, and Microcystis toxin gene (mcyD) abundance in LO and SLE during the massive bloom in July 2016, the bloom in August 2017 (two weeks before Irma), and 10 days after Hurricane Irma landfall. In 2016, cyanoHABs were present in both LO and SLE, and potential NH4+ uptake rates were high in both systems. In 2017, the bloom was constrained to LO, and potential NH4+ uptake rates in LO exceeded those in SLE, and mcyD gene abundance was greater in LO than SLE. Post Hurricane Irma, potential NH4+ uptake rates decreased significantly in LO and SLE, while mcyD gene abundance decreased in LO and increased slightly in SLE. Average NH4+ regeneration rates could support 25–40% of water column potential NH4+ demand in the lake and, when extrapolated to the entire LO water column, exceeded external nitrogen loading. These results emphasize the importance of internal NH4+ recycling for bloom expansion and toxicity in the lake and downstream estuaries. In 2018, the cyanobacterial bloom in the Okeechobee region was one of the largest recorded and is presumed to be driven by the aftermath of Hurricane Irma. Large-scale blooms have also been observed in SLE, likely due to LO flushing and decreased salinity post hurricane. Thus, results from this study support predictions that increased frequency and strength of tropical storms will lead to more intense blooms in aquatic systems.